Causes and Clinical Outcomes in Neonates with Acute Abdomen Requiring Surgery at Muhimbili National Hospital Dar es Salaam (Tanzania Medical Journal, 2015)
Background: Acute abdomen is a common surgical problem in neonates and often presents as a diagnostic dilemma for primary clinicians. Neonatal surgery is challenging, particularly in the emergency setting whereby problems like misdiagnosis with serious consequences occur thereby accounting for high morbidity and mortality in neonates. There are few reports from Sub-Saharan Africa about the magnitude and consequences of acute surgical abdominal emergencies in neonates. Objective: The aim of this study was to determine the causes and clinical outcomes in neonates with acute abdomen requiring surgery at Muhimbili National Hospital (MNH) in Dar-es-salaam, Tanzania. Methodology: This was a one year prospective hospital based study of all neonates (? 30 days old) who underwent surgery for acute abdominal emergencies at Muhimbili National Hospital paediatric surgery unit from January 2009 to December 2009. All neonates who were operated for acute abdomen were recruited into the study. Data on patient’s profile, duration of symptoms, causes of acute surgical abdomen, clinical outcomes, duration of hospitalisation and reasons for delayed presentation to hospital (MNH) were recorded and analysed. Results: A total of 43 neonates were studied, boys were the majority being 28 out of 43 (65.1%) and the male to female ratio was 1.9:1. Neonatal intestinal obstruction was the main abdominal surgical emergency accounting for 38 of the 43 neonates (88.4 %). Other causes included peritonitis (6.9%) and abdominal wall defects (4.7%).The most common postoperative complication was wound sepsis accounting for 13 cases (30.2%) and mortality was 34.9 % ( 15 neonates). High mortality was observed in those who developed peritonitis (66.7%). Wound sepsis and mortality were high among neonates who even presented early to hospital (32% and 36.0% respectively). However, these findings were not statistically significant (p>0.05). The main reason for delayed presentation was misdiagnosis at primary and secondary health facilities (59.3%). Conclusions and Recommendations: Intestinal obstruction was the major cause of acute surgical abdominal emergencies in Neonates. Neonates who presented early to hospital had similar morbidity and mortality to the late presenters in this study. Misdiagnosis at primary health facilities was the main reason for delayed presentation to hospital (MNH). Therefore there is a need to improve on neonatal surgical diagnosis and care at both primary and secondary health facilities in order to promote early referral of neonates in stable condition. Ensuring skilled and dedicated staff with improved facilities like neonatal ventilators, parenteral nutrition, a specialised neonatal operating theatre and intensive care unit (NICU) at MNH will greatly minimise morbidity and help reduce mortality.